The Nursing Care for Decreased Cardiac Output with Nursing Intervention: Measurement of Fluid Intake and Output in CHF Patients at Menggala Regional General Hospital - Serly Agustina; Sugiarto Sugiarto (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Patients with congestive heart failure (CHF) commonly experience shortness of breath due to impaired myocardial contractility, which leads to reduced cardiac output and subsequently decreases systemic blood circulation. This condition can result in several complications such as dyspnea, orthopnea, exertional dyspnea, paroxysmal nocturnal dyspnea (PND), edema, ascites, cardiogenic shock, and decreased oxygen saturation. Patients who exhibit clinical signs and symptoms of heart failure often present with actual or potential nursing problems, which can affect basic human needs, such as decreased cardiac output. One of the appropriate nursing interventions for this issue is monitoring the patient’s daily fluid intake and output. The aim of this study is to determine the effectiveness of the nursing intervention of fluid intake and output monitoring in hospitalized CHF patients. Method: This study employs a descriptive approach using a case study design. The respondents in this case were two patients diagnosed with CHF. The nursing intervention involved measuring the patients’ fluid intake and output over a 24-hour period and evaluating the outcomes by calculating fluid balance. Result: The results of the nursing care showed that Patient 1 had a fluid balance of -300 ml and Patient 2 had a fluid balance of -580 ml. Conclusion: These findings suggest that the intervention of fluid intake and output monitoring can be applied to CHF patients to improve their quality of life.